Programmed cell death markers in COVID-19 survivors with and without sepsis - Mallarpu, Chandra Shekar; Chelluri, Srinivasa Ikswaja; Katragadda, Tapaswi Krishna; Singarapu, Maneendra; Chelluri, Lakshmi Kiran; Madiraju, Charitha (Frontiers in Immunology, 2025)
IntroductionSepsis remains a leading cause of mortality, especially in COVID-19 patients, due to delayed diagnosis and limited therapeutic options. While the mechanisms of programmed cell death (PCD) in COVID-19 and sepsis are complex, understanding the molecular markers involved in these processes may aid in assessing disease severity. This study aimed to investigate the roles of PCD markers, inflammatory cytokines, and MHC molecules in distinguishing disease severity in COVID-19 patients with and without sepsis.MethodsThe study involved adult patients (≥18 years) who survived COVID-19, grouped into four cohorts: COVID-19 with sepsis (C19wSepsis), COVID-19 without sepsis (C19NoSepsis), sepsis alone, and healthy controls. Serum and peripheral blood mononuclear cells (PBMCs) from each cohort were analyzed using enzyme-linked immunosorbent assay (ELISA) and flow cytometry. PCD markers (caspase-3, caspase-1, MLKL, LC3B, p62/SQSTM1), inflammatory cytokines (IL-1-beta, IFN-gamma), and MHC molecules (MHC I-A, MHC II-DRB1) were assessed. Statistical analyses were performed to evaluate differences in marker levels between and within cohorts.ResultsThe analysis identified two distinct molecular signatures associated with disease severity. The first signature, characterized by elevated levels of secreted markers of PCD, IL-1-beta, IFN-gamma, MHC I-A and MHC II-DRB1, was common to the C19wSepsis and C19NoSepsis cohorts. The second signature, which was more prominent in the cellular markers of PCD (caspase-1, caspase-3, MLKL, p62/SQSTM1), was uniquely associated with the C19wSepsis cohort.ConclusionThese findings provide insight into the molecular signatures distinguishing immune responses in COVID-19-related sepsis and may serve as valuable biomarkers for assessing disease severity, while guiding therapeutic interventions in critical care settings.